AKUNTABILITAS PELAYANAN TERHADAP KEPUASAN MASYARAKAT DI KANTOR KECAMATAN DUA PITUE KABUPATEN SIDENRENG RAPPANG - Murdiono Murdiono (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2017)
This study aims to determine service accountability to community satisfaction at the Dua Pitue District Office, Sidenreng Rappang Regency and to determine the factors influencing service accountability to community satisfaction at the Dua Pitue District Office, Sidenreng Rappang Regency. The data collection techniques used in this study were (1) observation, (2) interviews, (3) questionnaires, (4) document review. The collected data is then analyzed through frequency and percentage tables. The population of this study is the community as many as 61 people. The results showed that the Service Accountability used for community satisfaction at the Dua Pitue District Office, Sidenreng Rappang Regency, namely the service accountability indicator was considered very good, namely 78.67%, the community satisfaction indicator was considered quite good, namely 72.87%. the influence of service ethics in the fairly good category is 73.75%, the parentalism culture in the very good category with a percentage of 76.5%, and the influence of public control in the quite good category, which is 65%.